MHY1 Encodes a C(2)H(2)-Type Zinc Finger Protein That Promotes Dimorphic Transition in the Yeast Yarrowia lipolytica - Hurtado, Cleofe A. R. (American Society for Microbiology, 1999)
The yeast-to-hypha morphological transition (dimorphism) is typical of many pathogenic fungi. Dimorphism has been attributed to changes in temperature and nutritional status and is believed to constitute a mechanism of response to adverse conditions. We have isolated and characterized a gene, MHY1, whose transcription is dramatically increased during the yeast-to-hypha transition in Yarrowia lipolytica. Deletion of MHY1 is viable and has no effect on mating, but it does result in a complete inability of cells to undergo mycelial growth. MHY1 encodes a C(2)H(2)-type zinc finger protein, Mhy1p, which can bind putative cis-acting DNA stress response elements, suggesting that Mhy1p may act as a transcription factor. Interestingly, Mhy1p tagged with a hemagglutinin epitope was concentrated in the nuclei of actively growing cells found at the hyphal tip.